Bacterial profile in children with early childhood caries - Sinta Dwi ARDIYANTINI; Hening Tjaturina PRAMESTİ; Meirina GARTIKA (Dentistry Faculty, 2022)
Early Childhood Caries (ECC) is the most common chronic infectious disease of childhood in the world, caused by the interaction of the host (oral cavity), substrate, microbes, and time. Bacteria as microbes that play a role in the formation of ECC have been widely studied. This study aims to determine the bacterial profile in children with ECC and to compare the oral microbial profiles in children with ECC and caries-free children (CF). Methods: This study uses a scoping review method. Article searches were performed on the PubMed, Science Direct, Cochrane, and Google Scholar databases, using the keyword and Boolean operator